ASSESSMENT OF OVERWINTERING AND LOCAL REPRODUCTION CONDITIONS OF THE EPIDEMIOLOGICALLY DANGEROUS MOSQUITO SPECIES AEDES ALBOPICTUS (DIPTERA: CULICIDAE) IN SOUTH OF UKRAINE - Рудик, В.; Коржов, Є.; Чеботар, С. (SWorldJournal, 2024)
Background: The rapid spread of Aedes albopictus (Skuse, 1895) is a global medical concern due to its ability to carry more than 30 pathogens. Global climate change contributes to the potential expansion of the range of the tropical species in the temper